A dynamic scanning method based on signal‐statistics for scanning electron microscopy. Issue 3 (28th June 2013) - Timischl, F.
Summary A novel dynamic scanning method for noise reduction in scanning electron microscopy and related applications is presented. The scanning method dynamically adjusts the scanning speed of the electron beam depending on the statistical behavior of the detector signal and gives SEM images with uniform and predefined standard deviation, independent of the signal value itself. In the case of partially saturated images, the proposed method decreases image acquisition time without sacrificing image quality. The effectiveness of the proposed method is shown and compared to the conventional scanning method and median filtering using numerical simulations. SCANNING 36:317–326, 2014. © 2013 Wiley Periodicals, Inc.